2022
DOI: 10.1021/acs.biomac.2c00400
|View full text |Cite
|
Sign up to set email alerts
|

Anionically Functionalized Glycogen Encapsulates Melittin by Multivalent Interaction

Abstract: We developed acid-functionalized glycogen conjugates as supramolecular carriers for efficient encapsulation and inhibition of a model cationic peptide melittin�the main component of honeybee venom. For this purpose, we synthesized and characterized a set of glycogens, functionalized to various degrees by several different acid groups. These conjugates encapsulate melittin up to a certain threshold amount, beyond which they precipitate. Computer simulations showed that sufficiently functionalized conjugates ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Studies can be found also of the complementary case, a strong PE adsorbing onto a weak charged object, including adsorption of the strong PE onto Janus particles [ 203 ], nanoparticles [ 162 , 204 , 205 ] and globular proteins [ 70 , 74 , 206 , 207 , 208 ]. The case when both the PE and the charged object can charge-regulate has only recently been studied using constant pH simulations [ 209 , 210 , 211 ]. They mutually enhance each other’s ionization, ultimately leading to different features than when only one component can charge-regulate.…”
Section: Adsorption Of Weak Polyelectrolytes Onto Charged Objectsmentioning
confidence: 99%
“…Studies can be found also of the complementary case, a strong PE adsorbing onto a weak charged object, including adsorption of the strong PE onto Janus particles [ 203 ], nanoparticles [ 162 , 204 , 205 ] and globular proteins [ 70 , 74 , 206 , 207 , 208 ]. The case when both the PE and the charged object can charge-regulate has only recently been studied using constant pH simulations [ 209 , 210 , 211 ]. They mutually enhance each other’s ionization, ultimately leading to different features than when only one component can charge-regulate.…”
Section: Adsorption Of Weak Polyelectrolytes Onto Charged Objectsmentioning
confidence: 99%
“…17 Glycogen can be degraded to smaller particle sizes through mild acid hydrolysis, 18 and, on the other hand, glycogen chains can be extended through enzymatic chain elongation, though this commonly leads to hydrogel materials as particles form stronger interactions together. 19 The nanoparticles have high water retention due to the abundance of closely-packed hydroxyl groups, 13 and can be functionalised to stick to most surfaces, 20 to inhibit corrosion, 21 to exhibit anti-inflammatory properties, 22 and encapsulating hydrophobic phases and vitamins, 23,24 antidotes, 25 amongst so much more. Whilst other biomaterials have been actively pursued in the nanomedicine space, including linear cellulose and branched starch polysaccharides, these other biomaterials lack the combined properties that are inherent to glycogen in its native nanoparticle form.…”
Section: Introductionmentioning
confidence: 99%